Does Analytic Thinking Insulate Against Pro‐Kremlin Disinformation? Evidence From Ukraine. Issue 1 (22nd May 2022) - Erlich, Aaron; Garner, Calvin; Pennycook, Gordon; Rand, David G.
Abstract : Pro‐Kremlin disinformation campaigns have long targeted Ukraine. We investigate susceptibility to this pro‐Kremlin disinformation from a cognitive‐science perspective. Is greater analytic thinking associated with less belief in disinformation, as per classical theories of reasoning? Or does analytic thinking amplify motivated system 2 reasoning (or "cultural cognition"), such that analytic thinking is associated with more polarized beliefs (and thus more belief in pro‐Kremlin disinformation among pro‐Russia Ukrainians)? In online ( N  = 1, 974) and face‐to‐face representative ( N  = 9, 474) samples of Ukrainians, we find support for the classical reasoning account. Analytic thinking, as measured using the Cognitive Reflection Test, was associated with greater ability to discern truth from disinformation—even for Ukrainians who are strongly oriented towards Russia. We find similar, albeit weaker, results when operationalizing analytic thinking using the self‐report Actively Open‐Minded Thinking scale. These results demonstrate a similar pattern to prior work using American participants. Thus, the positive association between analytic thinking and the ability to discern truth versus falsehood generalizes to the qualitatively different information environment of postcommunist Ukraine. Despite low trust in government and media, weak journalistic standards, and years of exposure to Russian disinformation, Ukrainians who engage in more analytic thinking are better able to tell truth from falsehood.